Standard pancreatoduodenectomy versus extended pancreatoduodenectomy with modified retroperitoneal nerve resection in patients with pancreatic head cancer: a multicenter randomized controlled trial. Issue 2 (29th December 2022) - Lin, Qing; Zheng, Shangyou; Yu, Xianjun; Chen, Meifu; Zhou, Yu; Zhou, Quanbo; Hu, Chonghui; Gu, Jing; Xu, Zhongdong; Wang, Lin; Liu, Yimin; Liu, Qingyu; et al.
Abstract: Background: The extent of pancreatoduodenectomy for pancreatic head cancer remains controversial, and more high‐level clinical evidence is needed. This study aimed to evaluate the outcome of extended pancreatoduodenectomy (EPD) with retroperitoneal nerve resection in pancreatic head cancer. Methods: This multicenter randomized trial was performed at 6 Chinese high‐volume hospitals that enrolled patients between October 3, 2012, and September 21, 2017. Four hundred patients with stage I or II pancreatic head cancer and without specific pancreatic cancer treatments (preoperative chemotherapy or chemoradiation) within three months were randomly assigned to undergo standard pancreatoduodenectomy (SPD) or EPD, with the latter followed by dissection of additional lymph nodes (LNs), nerves and soft tissues 270° on the right side surrounding the superior mesenteric artery and celiac axis. The primary endpoint was overall survival (OS) by intention‐to‐treat (ITT). The secondary endpoints were disease‐free survival (DFS), mortality, morbidity, and postoperative pain intensity. Results: The R1 rate was slightly lower with EPD (8.46%) than with SPD (12.56%). The morbidity and mortality rates were similar between the two groups. The median OS was similar in the EPD and SPD groups by ITT in the whole study cohort (23.0 vs. 20.2 months, P = 0.100), while the median DFS was superior in the EPD group (16.1 vs. 13.2 months, P = 0.031). Patients with preoperative CA19–9 < 200.0 U/mL had significantly improved OS and DFS with EPD (EPD vs. SPD, 30.8 vs. 20.9 months, P = 0.009; 23.4 vs. 13.5 months, P < 0.001). The EPD group exhibited significantly lower locoregional (16.48% vs. 35.20%, P < 0.001) and mesenteric LN recurrence rates (3.98% vs. 10.06%, P = 0.022). The EPD group exhibited less back pain 6 months postoperation than the SPD group. Conclusions: EPD for pancreatic head cancer did not significantly improve OS, but patients with EPD treatment had significantly improved DFS. In the subgroup analysis, improvements in both OS and DFS in the EPD arm were observed in patients with preoperative CA19–9 < 200.0 U/mL. EPD could be used as an effective surgical procedure for patients with pancreatic head cancer, especially those with preoperative CA19–9 < 200.0 U/mL.